Natural fate and freedom : a critical examination of Habermas' intuitions on autonomy and enhancements - Soh, Michael Anderson Sheng Rong (Nanyang Technological University, 2021)
This paper is written in order to examine the intuitions presented by Jürgen Habermas his 2003 publication The Future of Human Nature. In his book, Habermas outlines his intuitions regarding the requisites for an individual to possess complete autonomy, as well as how genetic enhancements undermine the autonomy of the enhanced persons. In this paper, I will contend that many of the intuitions Habermas has which leads to the formation of his arguments contain inconsistencies that he has to either resolve or concede that it might be possible under certain circumstances for the full autonomy of an enhanced person to be retained.